Prognostic Impact of Left Atrial Function Following Transcatheter Mitral Valve Repair. Issue 9 (7th May 2019) - Ledwoch, Jakob; Leidgschwendner, Katharina; Fellner, Carmen; Poch, Felix; Olbrich, Ida; Thalmann, Ruth; Kossmann, Hans; Dommasch, Michael; Dirschinger, Ralf; Stundl, Anja; Laugwitz, Karl‐Ludwig; Kupatt, Christian; et al.
Abstract : Background: Left atrial (LA) function predicts clinical outcome in a variety of cardiovascular diseases. However, limited data are available in the setting of mitral regurgitation. The aim of the present study was to assess potential changes in LA ejection fraction (LAEF) and its prognostic value in patients following transcatheter mitral valve repair using the MitraClip. Methods and Results: A total of 88 consecutive patients undergoing MitraClip implantation with complete echocardiography at baseline and follow‐up between 3 and 6 months postprocedure were enrolled. LAEF improved in 58% of the population. Change in LAEF was associated with residual mitral regurgitation, residual transmitral gradient and left ventricular ejection fraction changes. Compared with their counterparts, patients with residual mitral regurgitation ≥grade 2 (change in LAEF, −6% [Interquartile [IQR], −9–1%] versus 4% [IQR, −5–15%]; P =0.05) and with residual transmitral gradient ≥5 mm Hg (change in LAEF, −2% [IQR, −9–9%] versus 5% [IQR, −4–16%]; P =0.03) showed a decline in LAEF, respectively. Furthermore, LAEF significantly correlated with changes in left ventricular ejection fraction ( r =0.40; P =0.001). With regards to clinical outcome, heart failure symptoms as assessed by New York Heart Association class were more severe in patients with worsened LAEF at follow‐up. Finally, LAEF change was identified as an independent predictor of all‐cause mortality (hazard ratio, 0.94; 95% CI, 0.90–0.98 [ P =0.008]). Conclusions: The present analysis showed that changes in LA function in patients undergoing MitraClip implantation are associated with important measures including residual mitral regurgitation, elevated transmitral gradient, and left ventricular function. Importantly, LA function alterations represent a strong predictor for all‐cause mortality.